PER-VAGINAL DELIVERY OF ANASARCOUS FOETUS IN A TELLICHERRY DOE - CHANDRASEKARAN, D; SELVAKUMAR, S; SURESH KUMAR, R; POTHIAPPAN, P; KUMAR DAS, ANANGA; BALASUBRAMANIAN, S (The Indian Journal of Animal Reproduction, 2023)
A successful per-vaginal delivery of an anasarcous foetus with breech presentation was reported in aTellicherry doe.
Keywords: Foetal anasarca; Per-vaginal delivery; Generalized edema; Tellicherry doe; Single foetus